Global carbon uptake of cement carbonation accounts 1930–2021 - Z. Huang; Z. Huang; J. Wang; J. Wang; J. Wang; L. Bing; L. Bing; L. Bing; Y. Qiu; R. Guo; Y. Yu; M. Ma; et al. (Earth System Science Data, 2023)
The main contributor to the greenhouse gas (GHG) footprint of the cement industry is the decomposition of alkaline carbonates during clinker production. However, systematic accounts for the reverse of this process – namely carbonation of calcium oxide and other alkaline oxides and/or hydroxides within cement materials during cements' life cycles – have only recently been undertaken. Here, adopting a comprehensive analytical model, we provide the most updated estimates of CO2 uptake by cement carbonation. The accumulated amount of global CO2 uptake by cements produced from 1930 to 2021 is estimated to be 22.9 Gt CO2 (95 % confidence interval, CI: 19.6–26.6 Gt CO2). This amount includes the CO2 uptake by concrete, mortar, construction waste and kiln dust, accounting for 30.1 %, 58.5 %, 4.0 % and 7.1 % respectively. The cumulative carbon uptake by cement materials from 1930 to 2021 offsets 55.1 % of the emissions from cement production (41.6 Gt CO2, 95 % CI: 38.7–47.2 Gt CO2) over the same period, with the greater part coming from mortar (58.5 % of the total uptake). China has the highest cement carbon uptake, with cumulative carbonation of 7.06 Gt CO2 (95 % CI: 5.22–9.44 Gt CO2) since 1930. In addition, the carbon uptake amounts of the USA, EU, India and the rest of the world took 5.0 %, 23.2 %, 5.6 % and 34.8 % separately. As a result of rapidly increased production in recent years, over three-quarters of the cement carbon uptake has occurred since 1990. Additionally, our results show little impact by the COVID-19 pandemic on cement production and use, with carbon uptake reaching about 0.92 Gt CO2 (95 % CI: 0.78–1.10 Gt CO2) in 2020 and 0.96 Gt CO2 (95 % CI: 0.81–1.15 Gt CO2) in 2021. Our uniformly formatted and most updated cement uptake inventories provide coherent data-based support for including cement carbon uptake into future carbon budgets from the local to global scale. The latest version contains the uptake data till 2021, showing the global uptake's increasing pattern and offering more usable and relevant data for evaluating cement's carbon uptake capacity. All the data described in this study are accessible at https://doi.org/10.5281/zenodo.7516373 (Bing et al., 2023).